Diseño de vestidos de gala, basados en el análisis semiótico de la vestimenta Tsáchila - Carrera Noriega, Evelyn Janeth (2020)
The design in Ecuadorian fashion has denoted several weaknesses, from brands of clothing or accessories that do not have an added value to the product that identifies them and distinguishes them from the rest and the lack of value for what is done in the country. This project is about the design of a collection of gala dresses, which is inspired by the clothing of the Tsa'chila nationality, where different elements such as shapes, accessories and colors are taken, this in order to obtain an original product and In addition, take advantage of the country's cultural wealth, which offers great possibilities when proposing designs, in this case the clothing. In the same way, research was used, which is the first tool that allows the designer, the construction of ideas, collect theoretical and visual information, in addition to being able to interpret countless silhouettes, details, colors, textures, ornaments that allow the development of the creative process of the collection. It is necessary to take into account, that essential part of the investigation, is the study of the market and target audience to which the product is going to be offered. To conclude, it is in this way that a collection of prom dresses with originality, elegance, glamor and the taste of a target audience was obtained.